Correlation of endometrial thickness using transvaginal sonography with histopathology in women with abnormal uterine bleeding: A cross-sectional study - Rajlaxmi Mundhra; Kumari, Prerna; Bahadur, Anupama; Chawla, Latika; Singh, Rajni; Dibna Sinha; Gupta, Dipesh; Chaturvedi, Jaya (Asian Journal of Medical Sciences, 2023)
Background: Abnormal uterine bleeding (AUB) is one of the most common complaints seen in gynecological practice, and transvaginal sonography (TVS) remains the first-line, non-invasive diagnostic tool in these women. Aims and Objectives: The aim was to study the endometrial thickness (ET) using TVS and correlate it with histopathological findings obtained through endometrial biopsy in patients with AUB. Materials and Methods: This was a prospective observational study conducted in a tertiary care center in Northern India, from January 2018 to June 2019. One hundred and sixty women in the reproductive age group presenting AUB were recruited. TVS was done to note (ET) and its echotexture with additional findings such as uterine, adnexal, or other pelvic pathology. The patient underwent endometrial aspiration using Karman Cannula, and its findings were correlated with TVS. Results: In our study, a majority of patients (40%, n=64) presenting with AUB belonged to the age group of 41–45 years, with fibroid being the most common cause (39.3%, n=63). Thickened ET (>12 mm) was noted in 44 (27.5%) patients and 4 had an endometrial polyp. The mean ET was 11.48±5.11 mm (range: 4–35 mm). The most common normal histopathology noted was secretory endometrium (29.37%, n=47), followed by proliferative endometrium (20.6%, n=33). The abnormal changes included disordered proliferative endometrium (23.1% n=37) and simple endometrial hyperplasia (6.8%, n=11). Four cases were found to have endometrial adenocarcinoma. On correlating TVS with histopathology, it was noted that out of 8 patients with ET of >20 mm, 3 patients had endometrial carcinoma, 2 had disordered proliferative endometrium, and 1 each had pill endometrium, normal secretory, and atypical hyperplasia. Conclusion: TVS provides crucial information on echo-morphological features of the uterine cavity, and increasing ET mandates histopathological confirmation for ruling malignancy.